2015
DOI: 10.1177/1932296815577424
|View full text |Cite
|
Sign up to set email alerts
|

Does Visceral Fat Estimated by Dual-Energy X-ray Absorptiometry Independently Predict Cardiometabolic Risks in Adults?

Abstract: Background: Abdominal visceral fat, typically measured by computer tomography (CT) or magnetic resonance imaging (MRI), has been shown to correlate with cardiometabolic risks. The purpose of this study was to examine whether a newly developed and validated visceral fat measurement from dual-energy X-ray absorptiometry (DXA) provides added predictive value to the cross-sectional differences of cardiometabolic parameters beyond the traditional anthropometric and DXA adiposity parameters. Method: A heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Fat distribution can be assessed by using dual-energy X-ray absorptiometry (DXA) [23], computed tomography (CT), or magnetic resonance imaging (MRI) scans but the high costs and sophistication of these methods limit their feasibility in clinical practice and other simpler methods have been used. In the current study, CT abdomen was performed in order to accurately assess trunk obesity and in order to assess the validity of CI in assessment of trunk obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat distribution can be assessed by using dual-energy X-ray absorptiometry (DXA) [23], computed tomography (CT), or magnetic resonance imaging (MRI) scans but the high costs and sophistication of these methods limit their feasibility in clinical practice and other simpler methods have been used. In the current study, CT abdomen was performed in order to accurately assess trunk obesity and in order to assess the validity of CI in assessment of trunk obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have demonstrated that increased visceral fat assessed by dual-energy X-ray absorptiometry (DXA) or by the gold-standard methods, such as computed tomography and magnetic resonance, is associated with a cluster of cardiometabolic abnormalities including dyslipidemia, insulin resistance, and inflammation in CKD patients [23], but the high costs and sophistication of these methods limit their feasibly in clinical practice, and other simpler methods like anthropometric measures have been used.…”
Section: Introductionmentioning
confidence: 99%
“…VAT is associated with a range of risk factors for lifestyle‐related diseases, such as insulin sensitivity and triglyceride and cholesterol levels (Bi et al, ; Rothney et al, ; Sasai et al, ). Eighteen (17.5%) participants with BN and 33 (62.3%) participants with BED had VAT levels above a previous suggested normative, healthy level of 300 g (Bosch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects who met inclusion criteria were seen as outpatients at the NIH CRC for measurements including: body weight, height, heart rate and blood pressure, as described above. Whole body and visceral fat mass was performed by dual‐energy x‐ray absorptiometry (GE Lunar iDXA, GE Healthcare, Madison, WI; software GE enCore 15 with CoreScan algorithm) . An insulin‐modified 3‐hour frequently sampled intravenous glucose tolerance test (FSIVGTT) was performed in the morning after an overnight fast as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Whole body and visceral fat mass was performed by dual-energy x-ray absorptiometry (GE Lunar iDXA, GE Healthcare, Madison, WI; software GE enCore 15 with Cor-eScan algorithm). 24 An insulin-modified 3-hour frequently sampled intravenous glucose tolerance test (FSIVGTT) was performed in the morning after an overnight fast as described previously. 25,26 Briefly, two intravenous catheters were placed in the antecubital veins, one for the administration of glucose and insulin, and the other for blood sampling from the contralateral arm.…”
Section: Initial Assessmentmentioning
confidence: 99%